Ensuring Participatory Design Through Free, Prior and Informed Consent: A Tale of Indigenous Knowledge Management System - Tariq, Zaman; Yeo, Alvin Wee (Springer, 2014)
Information and Communication Technologies (ICT) for Development is a growing field of study. There has also been an increasing interest in how access to ICT, such as connecting to the Internet, might impact social and economic development by, for example, giving access to unlimited knowledge (e.g. e-learning), providing health-related services (telediagnosis), offering businesses opportunities (e-commerce), employment opportunities, and access to government services (e-Government websites) (Siew, Yeo, & Zaman, 2013). In all such development projects, two critical success factors are the degree of the users’ satisfaction of the technology and the degree to which the services offered by the technology address the primary needs of intended beneficiaries (Dearden, 2008).